2023
DOI: 10.3390/ijms24076249
|View full text |Cite
|
Sign up to set email alerts
|

Zinc/Cerium-Substituted Magnetite Nanoparticles for Biomedical Applications

Abstract: Numerous studies have reported the possibility of enhancing the properties of materials by incorporating foreign elements within their crystal lattice. In this context, while magnetite has widely known properties that have been used for various biomedical applications, the introduction of other metals within its structure could prospectively enhance its effectiveness. Specifically, zinc and cerium have demonstrated their biomedical potential through significant antioxidant, anticancer, and antimicrobial featur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Therefore, the addition of antibiotics does not lead to the formation of secondary iron oxide phases, such as maghemite or hematite. [12,13,40,41]. All samples were sterilized using UV radiation for 20 min, followed by their dispersion in sterile deionized water at a concentration of 2 mg/mL.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the addition of antibiotics does not lead to the formation of secondary iron oxide phases, such as maghemite or hematite. [12,13,40,41]. All samples were sterilized using UV radiation for 20 min, followed by their dispersion in sterile deionized water at a concentration of 2 mg/mL.…”
Section: Resultsmentioning
confidence: 99%
“…The antimicrobial assays performed are in accordance with previous studies [12,13,40,41]. All samples were sterilized using UV radiation for 20 min, followed by their dispersion in sterile deionized water at a concentration of 2 mg/mL.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…One of the manuscripts submitted for this Special Issue aims to improve the properties of magnetite nanoparticles by incorporating zinc and/or cerium ions into its crystal lattice. Biological evaluation showed that such incorporation led to the emergence of antioxidant, anticancer, and antimicrobial properties in the nanostructures, with the effectiveness depending on the type and concentration of ions used for replacement [ 6 ].…”
mentioning
confidence: 99%